Modulation of the N400 component in relation to hypomanic personality traits in a word meaning ambiguity resolution task. Issue 9 (7th June 2017) - Raucher‐Chéné, Delphine; Terrien, Sarah; Gobin, Pamela; Gierski, Fabien; Kaladjian, Arthur; Besche‐Richard, Chrystel
Abstract : Aim: High levels of hypomanic personality traits have been associated with an increased risk of developing bipolar disorder (BD). Changes in semantic content, impaired verbal associations, abnormal prosody, and abnormal speed of language are core features of BD, and are thought to be related to semantic processing abnormalities. In the present study, we used event‐related potentials to investigate the relation between semantic processing (N400 component) and hypomanic personality traits. Methods: We assessed 65 healthy young adults on the Hypomanic Personality Scale (HPS). Event‐related potentials were recorded during a semantic ambiguity resolution task exploring semantic ambiguity (polysemous word ending a sentence) and congruency (target word semantically related to the sentence). Results: As expected, semantic ambiguity and congruency both elicited an N400 effect across our sample. Correlation analyses showed a significant positive relationship between the Social Vitality subscore of the HPS and N400 modulation in the frontal region of interest in the incongruent unambiguous condition, and in the frontocentral region of interest in the incongruent ambiguous condition. Conclusion: We found differences in semantic processing (i.e., detection of incongruence and semantic inhibition) in individuals with higher Social Vitality subscores. In the light of the literature, we discuss the notion that a semantic processing impairment could be a potential marker of vulnerability to BD, and one that needs to be explored further in this clinical population.